Electrochemical Analysis of Proteins and Cells - Li, Genxi; Miao, Peng.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Electrochemical Analysis of Proteins and Cells presents the remarkable progress made over the years in the electrochemical analysis of proteins and cells, due to the rapid development of protein electrochemistry together with related technologies such as surface modification, molecular recognition, molecular assembly, and nanotechnology. As an interdisciplinary field combining electrochemistry, analytical chemistry, biochemistry, biophysics, biomedicine and material science, the electrochemical analysis of proteins and cells has attracted broad and extensive research interest. The main emphasis of this book is on the principles of electrochemical strategies and the practical utility of related detection systems, which is of great importance in all biological sciences, such as cell biology and molecular biology, as well as in biomedical fields like cancer research. This brief offers an up-to-date, easy-to-follow presentation of recent advances on the subject and can serve as a supplement for graduate-level courses in analytical chemistry, biochemistry, biophysics, biotechnology, biomedical engineering, etc. It may also help young scientists get an overview of this topic.
Introduction -- Theoretical Background of Electrochemical Analysis -- Electrochemical Analysis of Proteins -- Electrochemical Analysis of Cells.
Keywords: Chemistry; Analytical chemistry; Electrochemistry; Proteins; Biomedical engineering; Chemistry; Electrochemistry; Protein Science; Biomedical Engineering; Analytical Chemistry; Electronic books